2010
DOI: 10.1007/s10815-009-9381-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome analysis of mouse zygotes produced by intracytoplasmic injection of spermatozoa exposed to acrosome reaction inducing agents methyl-β-cyclodextrin and calcium ionophore A23187

Abstract: Purpose This study was performed to investigate whether removal of cholesterol from the plasma membrane and collapse of the acrosome can prevent structural chromosome aberrations of paternal origin in mouse zygotes produced by intracytoplasmic sperm injection (ICSI). Methods Mouse spermatozoa were treated with methyl-β-cyclodextrin (MβCD) to remove cholesterol from the plasma membrane and with calcium ionophore A23187 to collapse the acrosome. Chromosomes of zygotes derived from MβCD-and ionophore-treated sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Therefore, upon MβCD treatment, cholesterol efflux from the sperm plasma membrane, which results in lipid raft movement and loosening of the lipid bilayer structure (Watanabe & Kondoh, 2011), may have supported the observed higher bovine sperm decondensation, and subsequent development, after ICSI. Indeed, the highest rate of embryonic development was observed in this group-a result also reported in a mouse ICSI model using the same sperm pretreatment (Tateno, 2010). Similar results were recently described using glutathione (Lee et al, 2015) and lysolecithin (Zambrano et al, 2016) as sperm pretreatments, confirming the positive effect of pretreatment in promoting DNA decondensation and pronucleus formation.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, upon MβCD treatment, cholesterol efflux from the sperm plasma membrane, which results in lipid raft movement and loosening of the lipid bilayer structure (Watanabe & Kondoh, 2011), may have supported the observed higher bovine sperm decondensation, and subsequent development, after ICSI. Indeed, the highest rate of embryonic development was observed in this group-a result also reported in a mouse ICSI model using the same sperm pretreatment (Tateno, 2010). Similar results were recently described using glutathione (Lee et al, 2015) and lysolecithin (Zambrano et al, 2016) as sperm pretreatments, confirming the positive effect of pretreatment in promoting DNA decondensation and pronucleus formation.…”
Section: Discussionsupporting
confidence: 89%
“…The suspension was kept for 2 h at 378C under 5% CO 2 in air to capacitate the spermatozoa. Acrosome-reacted spermatozoa were obtained according to Tateno [22]. Briefly, epididymal spermatozoa were incubated in TYH for 5 min or 2 h, treated with 20 lM Ca 2þ ionophore (A23187) in 23 Ca 2þ TYH for 10 min, centrifuged, and allowed to swim out of the sperm pellet into 500 ll prewarmed TYH.…”
Section: Sperm Preparationmentioning
confidence: 99%
“…For example, induction of sperm capacitation [ 30 ] or the acrosome reaction [ 9 , 31 , 32 , 33 ] prior to ICSI was shown to improve the fertilization and/or development of the resultant zygotes. On the other hand, studies on mouse models revealed that the chromosomal integrity of zygotes derived from ICSI without any pretreatment of spermatozoa was impaired in comparison with that of zygotes derived from conventional IVF [ 12 , 34 , 35 ]. The damage was reduced by injecting spermatozoa cultured with bovine serum albumin or methyl-β-cyclodextrin [ 12 , 35 ], which triggered sperm capacitation due to cholesterol efflux on the plasma membrane [ 36 , 37 ].…”
Section: Risk Of Chromosomal Aberrations In Spermatozoa Present In Icmentioning
confidence: 99%
“…On the other hand, studies on mouse models revealed that the chromosomal integrity of zygotes derived from ICSI without any pretreatment of spermatozoa was impaired in comparison with that of zygotes derived from conventional IVF [ 12 , 34 , 35 ]. The damage was reduced by injecting spermatozoa cultured with bovine serum albumin or methyl-β-cyclodextrin [ 12 , 35 ], which triggered sperm capacitation due to cholesterol efflux on the plasma membrane [ 36 , 37 ]. Similarly, the frequency of chromosomal aberrations originating from sperm was low when spermatozoa were treated with calcium ionophore A23187 to induce the acrosome reaction [ 35 ].…”
Section: Risk Of Chromosomal Aberrations In Spermatozoa Present In Icmentioning
confidence: 99%
See 1 more Smart Citation